Pemerolehan Sintaksis Bahasa Minangkabau: Studi Kasus pada Seorang Anak Usia 3; 0–4; 0 - Emil Septia (Balai Bahasa Jawa Barat, 2017)
Every child is exposed to their mother language in the first stages of their lives. Thesyntax acquisition in children is very interesting to investigate. Sentences uttered bya child have a distinctive pattern that distinguishes it from those of the adult’s. Thechoice of words can also attract the attention of adults to understand better whatthe child said. The purpose of this study is to describe (1) the types of sentencesuttered by the child; (2) the child’s sentence patterns; (3) the speech form of thechild. The type of this research is descriptive qualitative research. The data are oraldata collected from the child’s speech recorded on a tape recorder and written on ajournal. The result shows that the types of sentences uttered by the child consist ofthree things. First, declarative, interrogative, and imperative sentences. Second, thechild’s sentence patterns are various, namely P, S-P, P-S, P-O, S-P-O, S-P-K, S-PPel,and S-P-O-K. Third, the child’s speech form consists of of one word, two words,three words, four words, and five words speech.AbstrakSetiap anak memperoleh bahasa ibu pada tahap pertama kehidupannya. Pemerolehansintaksis pada anak sangat menarik untuk diteliti. Kalimat-kalimat yang diujarkananak punya pola tersendiri yang membedakannya dari kalimat orang dewasa. Pilihankata yang digunakannya juga bisa menarik perhatian orang dewasa untuk lebihmemahami apa yang diujarkan anak tersebut. Tujuan penelitian ini adalah untukmendeskripsikan: (1) jenis-jenis kalimat yang diujarkan oleh anak; (2) pola kalimatanak; (3) bentuk ujaran anak. Jenis penelitian ini adalah penelitian kualitatif bersifatdeskriptif. Dalam pengumpulan data diperoleh data lisan bersumber dari ujarananak yang direkam dengan tape recorder dan dibuat sebuah catatan harian. Darihasil pengamatan, jenis-jenis kalimat yang diujarkan oleh anak terdiri atas pertamakalimat deklaratif, interogatif, dan imperatif. Kedua, pola kalimat pada ujaran anakberagam jenisnya, di antaranya P, S-P, P-S, P-O, S-P-O, S-P-K, S-P-Pel, dan S-PO-K. Ketiga, bentuk ujaran anak terdiri atas ujaran satu kata, dua kata, tiga kata,empat kata, dan lima kata.